The Gene Editing Platform of the Alliance of Bioversity International and CIAT - Sanchez, Francisco; Valdes, Sandra P.; Chavarriaga, Paul (2024)
Make gene editing tools like CRISPR an essential component of crop improvement for a more productive, nutritious agriculture, that protects biodiversity and the environment, and guarantees a constant food/feed supply